Engineering mechanics : Statics - Pytel, Andrew; Kiusalaas, Jaan. (Pacific Grove, CA : Brooks/Cole, 1999)
This book contains several optional topics about engineering mechanics.
Keywords: Mechanics; Statics; Statics; Mechanics, Applied